Transesterification of Jatropha curcas oil to biodiesel using highly porous sulfonated biochar catalyst: Optimization and characterization dataset - Supongsenla Ao (21633605) (2024)
The study involves a collection of data from the published article titled “Active sites engineered biomass-carbon as a catalyst for biodiesel production: Process optimization using RSM and life cycle assessment “Energy Conversion Management” journal. Here, the activated biochar was functionalized using 4-diazoniobenzenesulfonate to obtain sulfonic acid functionalized activated biochar. The catalyst was comprehensively characterized using XRD, FTIR, TGA, NH3-TPD, SEM-EDS, TEM, BET, and XPS analysis. Further, the obtained catalyst was applied for the transesterification of Jatropha curcas oil (JCO) to produce biodiesel. An experimental matrix was conducted using the RSM-CCD approach and the resulting data were analyzed using multiple regressions to fit a quadratic equation, where the maximum biodiesel yield achieved was 97.1 ± 0.4%, under specific reaction conditions: a reaction time of 50.3 min, a molar ratio of 22.9:1, a reaction temperature of 96.2 °C, and a catalyst loading of 7.7 wt.%. The obtained product biodiesel was analyzed using NMR and GC-MS analyzed and is reported in the above-mentioned article. Other Information Published in: Data in Brief License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.dib.2024.110096